Baddeley And Hitch's Multi-component Model Of Working Memory Analytical Study - Souliby Assia; Mahammedi Faouzia (University of Eloued جامعة الوادي, 2024)
. الملخـص بالعربية : هدفت الدراسة الحالية إلى تقديم نظرة واسعة وشاملة لنموذج بادلي للذاكرة العاملة والتي تعتبر حسب بادلي وحسب الدراسات الحديثة أنها الجزء النشط والفعال في الذاكرة وأنها ذات أهمية بالغة في تخزين ومعالجة وتجهيز المعلومات.ويعتبر نموذج بادلي من أهم النماذج التي أعدت في مجال الذاكرة العاملة، ومن النماذج التي لاقت رواجا ونجاحا كبيرين، حيث أعد بادلي وهيتش نموذجا للذاكرة العاملة سنة 1973، ثم قام بادلي بتعديله وتنقيحه سنة1986، حيث أعد بادلي نموذجه الأول سنة 1986 وهو نموذج ثلاثي يتكون من المنفذ المركزي وهو نظام مسؤول عن معالجة المعلومات وتخزينها، ويندرج تحته نظامان فرعيين، النظام الأول يسمى بالحلقة الفونولوجية وهو نظام مسؤول عن تجهيز المعلومات اللفظية، ويتكون من مكونين؛ الحلقة الفونولوجية، وعملية الضبط اللفظية. أم النظام الثاني يسمى بالمكون البصري المكاني، وهو مكون يتعامل مع المعلومات البصرية المكانية. وفي سنة 2000 قام بادلي بإضافة مكون جديد إلى نموذج الذاكرة العاملة أطلق عليه اسم مصد الأحداث أو الحاجز العرضي أو الجسر المرحلي، وبالتالي أصبح نموذج بادلي للذاكرة العاملة نموذج رباعي المكونات. Abstract: The current article seeks to provide a broad and comprehensive view of Baddeley's model of working memory. Baddeley and recent studies consider working memory to be the active and effective part of memory and of great importance in storing, processing, and preparing information .Baddeley's model is one of the most important models developed in the field of working memory, and it has been widely accepted and successful. Baddeley and Hitch developed a model of working memory in 1973, which Baddeley revised and refined in 1986. Baddeley's first model in 1986 was a tripartite model consisting of a central executive system responsible for processing and storing information, with two subsystems under it. The first system is called the phonological loop, which is a system responsible for processing verbal information and consists of two components: the phonological loop and the verbal control process. The second system is called the visuospatial component, which deals with visuospatial information.